Ecological media perspective on WhatsApp status features - Rosa Apriliyanti (Indonesian Journal of Social Sciences, 2020)
The presence of the internet today makes it easy for users to carry out communication activities without limitation of distance and time. Even instant messaging such as WhatsApp, which has the primary function as a medium for communication, can be a mediator for self-existence and cannot be separated from its users to share daily activities through the WhatsApp Status feature. The purpose of this study was to analyze the Status feature on Instant Messaging WhatsApp as a mediator to show self-existence without distance and time limits based on media ecology theory. The method in this study is a qualitative method with purposive data collection techniques. Researchers also conducted interviews with seven informants who were students and workers. This study's results indicate that the presence of this feature affects various actions, perceptions, and communication experiences in society. Ecological media has the perspective that electronic media has radically changed society. In essence, society is very dependent on technology that uses media, and that the social order of a society is based on its ability to deal with these technologies. Media, in general, act directly to form and organize culture. Apart from that, ecological media also has assumptions about how technology affects society, include the distinction between hot and cold media.